Extended Subtotal Mandibulectomy for the Treatment of Oral Tumors Invading the Mandibular Canal in Dogs—A Novel Surgical Technique - Fiani, Nadine; Peralta, Santiago (Frontiers in Veterinary Science, 2019)
Mandibular tumors in the oral cavity of dogs can be locally aggressive and infiltrative, involving adjacent soft and hard tissues. Tumors that invade the mandibular canal are considered likely to extend rostrally and caudally within that structure due to minimal tissue resistance. When this occurs, a total mandibulectomy is thought to be the treatment of choice as it allows en bloc excision of the mandibular canal. This procedure is technically challenging and time consuming. In the present report we describe a novel technique, the extended subtotal mandibulectomy, as a possible alternative in cases of mandibular body tumors that have invaded the mandibular canal. This technique allows the complete excision of the mandibular canal whilst retaining the coronoid and condylar processes.